Klasifikasi Bunga Melati dengan Menggunakan Local Binary Pattern - Sahril Amuda; Felix Indra Kurniadi (Teknik Informatika, 2019)
Jasmine is the one of the national flower. Each jasmine type has unique characteristic and different between each other. Sadly, Indonesia is not the only one who have the Jasmine as the national flower, the other countries such as Malaysia and Philippine have their jasmine. In this research we tried to classify between Indonesia and Other country Jasmine. We proposed using Local Binary Pattern as the feature extraction and K-Nearest Neighbour as the classifier. The result shows the best accuracy from our proposed methods is 55%.